Management and outcome of pancreatic trauma: a 6-year experience at a level I trauma center - Abhinav Anand; Parvez Mohi Ud Din Dar; Preksha Rani; Supreet Kaur; Joses Dany James; Junaid Alam; Pratyusha Priyadarshini; Abhinav Kumar; Dinesh Bagaria; Narendra Choudhary; Subodh Kumar; Amit Gupta; et al. (Emergency and Critical Care Medicine)
Abstract. Background. Pancreatic trauma (PT) accounts for less than 1% of all trauma admissions. Occasionally, PT is undetected during the primary survey and becomes apparent only when complications arise. It occurs in up to 5% of blunt abdominal trauma cases and 12% of individuals with penetrating abdominal injuries. Management is determined by the status of the main pancreatic duct and associated injuries. Methods. This was an ambispective study conducted at the Jai Prakash Narayan Apex Trauma Center, All India Institute of Medical Sciences, New Delhi, from January 2015 to December 2017 (retrospective), and January 2019 to December 2020 (prospective). In total, 113 patients with PT were included in this study. Results. We analyzed the data of 113 patients with PT included in this study, of which males predominated (93.7%). Blunt PT was present in 101 patients (89.4%) and penetrating PT in 12 patients (10.6%). Half of the patients (51.3%) had the American Association for the Surgery of Trauma grade III PT, followed by grade II (18.6%), and grade I (15%). Of the total 113 patients, 68 (60.2%) were treated with operative management, and 45 (39.8%) with nonoperative management. Distal pancreatectomy, with or without splenectomy, was the most common procedure performed in our study, followed by drainage. There were 27 mortalities (23.8%) during the study period, of which 7 were directly related to PT and 20 were due to other organ-related sepsis and hemorrhagic shock. Conclusion. Pancreatic trauma is rare but challenging for trauma surgeons, with persistent management controversies. Early diagnosis is important for favorable results; however, a delay in diagnosis has been associated with higher morbidity and mortality. Low-grade pancreatic injuries can be successfully managed nonoperatively, whereas high-grade pancreatic injuries require surgical intervention.